A heteropolysaccharide from Saccharina japonica with immunomodulatory effect on RAW 264.7 cells. (1st December 2018) - Geng, Lihua; Hu, Weicheng; Liu, Yingjuan; Wang, Jing; Zhang, Quanbin
Abstract: A heteropolysaccharide (SHP) with a strong immunomodulatory effect on RAW 264.7 cells was prepared from Saccharina japonica . Chemical analysis demonstrated that SHP was primarily composed of mannose, glucuronic acid, glucose, fucose, galactose, xylose and rahmnose with a molar ratio of 1.00:0.85:0.84:0.58:0.30:0.37:0.15. ESI-MS showed that depolymerized SHP produced oligo-glucuronan, oligo-glucuronomannan, sulfated fuco-oligosaccharides and other hetero-oligosaccharides. The in vitro immunomodulatory results showed that SHP could increase NO production and up-regulate the expression of many immune effectors, including iNOS, COX-2 and TNF-α, displaying an apparent immune enhancement activities. Western blot analysis proved that SHP activated the expression levels of many key components involved in NF-κB, MAPK and Akt signaling pathways. Our results together indicated that SHP has the potential to be developed as a novel immunomodulator for activating immune system.